Fundamentals of Traffic Simulation - Barceló, Jaume; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
The increasing power of computer technologies, the evolution of software engineering and the advent of Intelligent Transport Systems (ITS) worldwide has helped make traffic simulation one of the most used approaches for traffic analysis in support of the design and evaluation of traffic systems. The ability of traffic simulation software to emulate the time variability of traffic phenomena makes it a uniquely useful tool for capturing the complexity of traffic systems. While a wide variety of simulation software is available, no one book has presented a unified treatment of the subject. Fundamentals of Traffic Simulation is the first book to provide practitioners and researchers with a comprehensive treatment of the state of the art of traffic simulation. Leading researchers worldwide provide up-to-date information on: - Simulation as a well established and grounded OR technique and its specificities when applied to traffic systems. - The main approaches to traffic simulation and the principles of traffic simulation model building. - The fundamentals of traffic flow theory and its application to traffic simulation in Microscopic traffic modeling, Mesoscopic traffic modeling, and Macroscopic traffic modeling. - The principles of Dynamic Traffic Assignment and its application to traffic simulation. - The calibration and validation of traffic simulation models. This important work will appeal to professionals, including transport consultants, managers in design firms and government, and even simulation software developers. It will also provide researchers with the first comprehensive overview of the subject, and can serve as a text or recommended reading in courses on traffic simulation and transportation analysis.
Models, Traffic Models, Simulation, and Traffic Simulation -- Microscopic Traffic Flow Simulator VISSIM -- Traffic Simulation with AVENUE -- Traffic Simulation with Paramics -- Traffic Simulation with Aimsun -- Traffic Simulation with MITSIMLab -- Traffic Simulation with SUMO – Simulation of Urban Mobility -- Traffic Simulation with DRACULA -- Traffic Simulation with Dynameq -- Traffic Simulation with DynaMIT -- Traffic Simulation with METANET.
Keywords: Operations research; Decision making; Transportation; Regional planning; Urban planning; Management science; Regional economics; Spatial economics; Applied mathematics; Engineering mathematics; Operations Research/Decision Theory; Transportation; Landscape/Regional and Urban Planning; Operations Research, Management Science; Regional/Spatial Science; Mathematical and Computational Engineering